White Light Generating Molecular Materials: Correlation Between the Amorphous/Crystalline Structure and Nonlinear Optical Properties. Issue 6 (20th June 2022) - Haust, Johannes; Belz, Jürgen; Müller, Marius; Danilo Klee, Benjamin; Link Vasco, Jonathan; Hüppe, Franziska; Rojas Léon, Irán; Christmann, Jan; Beyer, Andreas; Dehnen, Stefanie; Rosemann, Nils W.; Pilgrim, Wolf‐Christian; et al.
Abstract: The front cover artwork is provided by Johannes Haust, Jürgen Belz, Kerstin Volz (Philipps‐University Marburg) and Sangam Chatterjee (Justus Liebig University Giessen). The image illustrates the generation of a transmission electron microscopy diffraction pattern from the amorphous adamantane‐type cluster compound [(PhSn)4 S6 ] (Ph=phenyl) as well as the conversion of red light from a continuous wave infrared laser into directed white light when propagating through the sample. Cover design by Elisa Monte. Read the full text of the Research Article at 10.1002/cptc.202200071 . Abstract : "We are interested in novel adamantane‐type cluster compounds. These materials show exceptional nonlinear optical properties, to date not fully understood, by either emitting highly directional white light or generating second harmonics when exited by a continuous wave laser diode. In this work we use transmission electron microscopy for structural investigation of these materials and correlate our results with their optical properties in order to acquire a better understanding of the principles leading to white light generation…" This and more about the story behind the front cover can be found in the Research Article at 10.1002/cptc.202200071 .